Book Review: The Empty Tank: Oil, Gas, Hot Air, and the Coming Global Financial Catastrophe. (10th May 2007) - Rhoades, Dawna L.
The Empty Tank: Oil, Gas, Hot Air, and the Coming Global Financial Catastrophe, by Jeremy Leggett. Random House, 2005. ISBN 1-4000-6527-5.